Personality and psychological well-being among cancer caregivers at the uganda cancer institute and mbarara regional referral hospital - Kansiime, Rachel; Mutto, Milton; Rukundo, Godfrey Zari; Niyonzima, Nixon; Orem, Jackson; Kizito, Simon (African Journal of Social Sciences and Humanities Research, 2022)
To assess the relationship between personality and psychological wellbeing among caregivers of patients with cancer in central and southwestern Uganda. Methods: A cross-sectional survey was conducted among adult caregivers of patients with cancer at the Uganda Cancer Institute in Kampala and at Mbarara Regional Referral Hospital in southwestern Uganda. The participants were consecutively recruited until a sample of 436 was reached. Personality was assessed using the NEO-Five Factor Inventory (NEO-FFI) after structural validation using exploratory factor analysis. On the other hand, psychological wellbeing was assessed using the General Health Questionnaire (GHQ-28). Data was analyzed using STATA version 14. The composite indices were summarized using measures of central tendency and spread. The relationship between the different subscales and the effect of personality on psychological wellbeing was assessed using multiple linear regression modelling. Results: After controlling for all the covariates, the personality domains of extroversion (P 0.0001, f statistic 4.26), neuroticism (P 0.0001, f statistic 4.31), openness (P 0.0000, f statistic 4.36) and introversion (P 0.0000, f statistic 4.31) influence psychological wellbeing of caregivers of patients with cancer. Conclusion: An individual’s personality is very crucial in cancer caregiving because it affects his/her psychological wellbeing. Therefore, it is important that the caregivers’ personality disposition is considered at the beginning and during the caregiving journey.
Keywords: Personality; Caregiver; Patient with cancer; Psychological well-being; Uganda